Ketahanan Komunitas Petani di Nagari Parambahan Pasca Bencana Lahar Dingin - Nurul Latifah (Lembaga Yasin AlSys, 2026)
The cold lava flow disaster of Mount Marapi has had significant impacts on the social and economic life of the community, particularly farming communities in Nagari Parambahan, Lima Kaum Subdistrict, Tanah Datar Regency, through the destruction of agricultural land, disruption of irrigation systems, loss of livelihoods, and declines in agricultural productivity that have tested community resilience in sustaining their livelihoods. This study aimed to analyze the resilience of farming communities in the aftermath of the cold lava flow disaster by examining adaptation strategies, socio-economic recovery processes, and empowerment efforts undertaken by the community and relevant stakeholders. The research employed a qualitative method with a descriptive approach, with data collected through in-depth interviews, field observations, and document studies, and informants selected using purposive sampling. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings show that the resilience of farming communities in Nagari Parambahan is at a moderate level, as reflected in livelihood diversification, the strengthening of social solidarity, and the utilization of government assistance, although the recovery process has not yet been optimal due to limited budgets, slow rehabilitation of agricultural land and infrastructure, and a lack of sustained technical assistance. This study concludes that post-disaster community resilience requires integrated, sustainable, and locally grounded policy support, with important implications for strengthening synergy between government, communities, and relevant institutions to ensure the sustainability of the agricultural sector in affected areas.